Reconsidering economics in relation to sustainable development and democracy - Peter Söderbaum (Editura ASE Bucuresti, 2019)
The challenge of sustainable development can be approached from different angles. In this essay it is argued that one also needs to examine the present close to monopoly position of neoclassical economic theory at university departments of economics in many parts of the world. An open debate is needed about paradigms in economics as well as ideological orientations. An alternative to neoclassical theory is outlined where individuals and organizations are regarded as political actors, each guided by an ideological orientation or mission. Reference is made to the 17 UN sustainable development goals suggesting that impacts need to be seen in multidimensional terms and an alternative definition of economics as “multidimensional management of limited resources in a democratic society” is proposed. It is argued that economics need to move away from its technocracy-oriented tendencies to democracy-oriented approaches. This is exemplified by a move away from neoclassical Cost-Benefit Analysis (CBA) to Positional Analysis as approach to decision-making and sustainability assessment.